A model of flops. (December 2013) - Hummel, Patrick; Morgan, John; Stocken, Phillip C.
<x xml:space="preserve">Abstract</x> A firm surveys a large number of consumers, some of whom sincerely report their tastes and others of whom report strategically. It makes product decisions using the sample mean of survey responses. When firms and consumers agree on the fraction of sincere consumers, information loss is severe, and many products are flops as they poorly match consumer tastes. When beliefs differ, however, equilibrium is in linear strategies, and information aggregates. Despite this, flops still arise. A firm, however, can solve the flops problem by limiting the effect of strategic consumers. Binary surveys offer one such solution.